Sosialisasi Dan Pelatihan Pembuatan Bakteri Fotosintesis (Synechococcus Sp.) Sebagai Penyubur Tanaman Di Desa Mojodanu - nasirudin, mohamad; Yuliana, Anggi Indah; Zuhria, Siti Aminatuz; Hartanti, Dyah Ayu Sri; Afdholi, Zakiyuddin Al; Alifadeyana, Laily; Fitriana, Dista; Ardiansya, Widi; Arif, Muhamad; Qomariyah, Umi Kulsum Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Training on making photosynthetic bacteria (Synechococcus sp.) as plant fertilizer aims to increase participants' knowledge and skills in utilizing photosynthetic microorganisms to support sustainable agriculture. Synechococcus sp., a type of cyanobacteria, has the ability to carry out photosynthesis and produce important nutrients such as nitrogen, which plays a role in increasing soil fertility. Through a service approach based on Participatory Action Research (PAR), this training involves active participation of participants in all stages of the process. This training covers various topics, starting from an introduction to the characteristics and benefits of Synechococcus sp. to isolation techniques, culture, and practical applications in agriculture. Participants are taught in depth how to process these bacteria and apply them to planting media with the aim of increasing productivity and plant health. In addition, participants were given an understanding of the importance of microorganisms in maintaining the balance of agricultural ecosystems. The training evaluation showed very positive results, with a significant increase in participants' understanding of the role of photosynthetic microorganisms in improving soil and plant quality. Participants' interest in applying this technique on their agricultural land was also very high, showing great potential for widespread application of this method. It is hoped that through this training, more environmentally friendly and sustainable agriculture can be created by utilizing biological resources, such as Synechococcus sp., to maintain soil health and support sustainable food production.